PENGARUH STRUKTUR AUDIT, KONFLIK PERAN DAN KETIDAKJELASAN PERAN TERHADAP KINERJA AUDITOR: (Studi Kasus Pada Kantor Akuntan Publik yang Terdaftar di IAPI Cabang Bandung) - Haryani Anggraeni; Imam Hadiwibowo (Jurnal Proaksi, 2017)
Auditor performance becomes main attention, well for client or public even,in assess audit result that is done. Auditor performance constitutes tousufruct job that reached by auditor in perform its task, according toaccountability which is given on it and as one ofrefuses fathom that is utilized todetermine, what a work that is done will well or on the contrary.Working condition that insufficiently conducive regards auditor performanceso get to regard society trust to public accountant as side as independentdeep audits financial statement. To the effect that wants to be reached in this research is subject to be knowstructure influence audits, role conflict and role vagueness to auditorperformance on enrolled Public Accountant Office at IAPI Bandung's Branch.Observational method that is utilized in this research is survey's method.Usufruct this observational conclusion which is audit structure (X1) havinginfluence that significant to auditor performance (Y). The results of this studysupport Zaenal Fanani (2007) that the audit structure significant effect on theauditor performance. Role conflict (X2) having influence that significant toauditor performance (Y). The results of this study support Zaenal Fanani (2007)that the role conflict significant effect on the auditor performance. Roleambiguity (X3) nots having influence to auditor performance (Y). The results ofthis study support Zaenal Fanani (2007) that the role ambiguity had nosignificant effect on the auditor performance. Structure audits (X1), role conflict(X2) and role ambiguity (X3) stimulant’s ala have influence that significant toauditor performance (Y).